Ten behaviors that will cost you your badge - Calibre Press; Trinity Workplace Learning; LETN (Firm) (Carrollton, TX : LETN, 2006)
Law enforcement personnel are constantly facing situations that test their personal values and moral character. This program outlines 10 behaviors that will absolutely cost you your badge.
Host, Lonny Wilder ; writers, Bill Quiett, Amy Mitchell.
DVD.
Keywords: Police; Police -- Personnel management; Police ethics; Law enforcement -- Moral and ethical aspects; Decision making -- Moral and ethical aspects